Hal Wallis : producer to the stars - Dick, Bernard F. (The University Press of Kentucky, 2015)
Hal Wallis might not be as well known as David O. Selznick or Samuel Goldwyn, but the films he produced -- Casablanca, Jezebel, Now Voyager, The Life of Emile Zola, Becket, True Grit, and many other classics (as well as scores of Elvis movies) -- have certainly endured. As producer of numerous films, Wallis made an indelible mark on the course of America's film industry, but his contributions are often overlooked and no full-length study has yet assessed his incredible career. A former office boy and salesman, Wallis first engaged with the business of film as the manager of a Los Angeles movie.